Profitabilitas Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia - Nurul Rizki; Abdul Hamid; Nurjanah (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
This study aims to see the effect of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on the profitability of BPRS in Indonesia. The research method used is a quantitative approach. The population of this research s all BPRS registered with the Financial Services Authority. By using purposive sampling there are as many as 6 BPRS used as samples in this study. The data analysis technique used in this study is panel data regression with the help of the Eviews 10 program. The result obtained indicate that partially the Capital Adequacy Ratio (CAR) has a negative and significant effect on profitability with a probability value of 0,0060 < 0,05. Non Performing Financing (NPF) has a positive and significant effect on profitability with a probability value of 0,0381 < 0,05. While the Financing to Deposit Ratio (FDR) has a positive and insignificant effect on profitability with a probability value of 0,7093 > 0,05. Simultaneously the independent variabel has a significant effect on the dependent variable with a significant value of 0,000000 < 0,05. This means that the Captal Adequacy Ratio (CAR), Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) simultaneously (together) have a significant effect on the profitability of BPRS in Indonesia.